APPLICATION OF MIND MAPPING LEARNING MODEL BASED ON HIGHER ORDER THINKING SKILLS (HOTS) ON CRITICAL THINKING ABILITY ON HUMAN AND ENVIRONMENTAL MATERIAL OF GRADE V STUDENTS OF SDN 04 SINGKAWANG - Setianingsih, Lilis; Sulistri, Emi; Fitriyadi, Slamat (PROGRES PENDIDIKAN, 2025)
This study aim to (1) identify students' critical thinking skills; (2) to identify differences in students' critical thinking skills; (3) to identify students' responses to the mind mapping learning model based on higher order thinking skills . Research This implemented at SDN 4 Singkawang . The data collection technique in this study used test and non- test techniques. that is in the form of a critical thinking ability test sheet for students and a student response questionnaire technique. The data analysis techniques used are Prerequisite Test, Hypothesis Test and N Gain . Based on results of hypothesis testing and two -sample t-test can known difference ability think critical students in class experiments and classes control . From the t-test shows t count > t table that is 4,322 > 2,024. Statement on can concluded that There are differences in the critical thinking abilities of students who are given the Mind Mapping learning model. based on Higher Order Thinking Skills and direct models on human and environmental material in class V of SD N 4 Singkawang. From the test data the improvement ability think critical students in class experiment with implementing learning models mind mapping experiencing improvement ability think critical students . Improvement the shown with N-gain acquisition of 0.64 with criteria in and out of class control with implementing learning models direct obtained an N-gain of 0.27 with criteria low . So by using the mind learning model mapping based on Higher Order Thinking Skills increased. Response students towards the mind learning model mapping based on Higher Order Thinking Skills of 80.93 in the very good criteria.